Oral, conjunctival and Auricular Kaposi’s sarcoma in a HIV-negative patient : an unusual presentation - Boubnane, Ibtissame; Jebli, Salma; Znati, Kaoutar; Senouci, Karima (International Journal of Research in Dermatology, 2023)
Kaposi’s sarcoma is an unusual multicentric malignant neoplastic disease, that characterized by the proliferation of spindle-shaped cells. This tumor is habitually involving in the skin of the lower extremities. However, it is rarely developing in the mucosa or skin of the head and neck. Herein, we report an uncommon presentation of Kaposi sarcoma affecting auricle,oral and ocula rmucosa in an immunocompetent patient. The diagnosis was made on clinical and histopathological finding.